Pengaruh Influencer Sosial Media, Brand Awareness Dan Brand Image Terhadap Brand Loyalty (Studi Pada Brand Fashion Ethica Fashion Store Malang) - Indriani, Iin; Djaelani, Abdul Kodir; Slamet, Afi Rachmat (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The aim of this research is to test and analyze whether Influencer Social Media, Brand Awareness and Brand Image simultaneously influence Brand Loyalty at the Ethica Fashion Store Malang. The type of research used in this research is a survey with a quantitative approach. The population in this study were Ethica Fashion Store customers in Malang. Sampling was based on the Malhotra formula and 75 respondents were obtained. This study uses multiple linear regression analysis using the SPSS 25 application. The results of the study indicate that there is a simultaneous influence between the Social Media Influencer variables (X1), Brand Awareness (X2) and Brand Image (X3) on Brand Loyalty (Study on the Brand Fashion Ethica Fashion Store Malang City). Partially, the Social Media Influencer variable does not have a significant effect on Brand Loyalty, while the Brand Awareness variable has a significant effect on Brand Loyalty, and the Brand Image variable does not have a significant effect on Brand Loyalty. Keywords: Influencer Social Media, Brand Awareness, Brand Image and Brand Loyalty